Penerapan Metode Waterfall dalam perancangan aplikasi sistem pembelian alat kesehatan berbasis Dekstop - Yuyun Yuningsih; Hilda Amalia; Ade Fitria Lestari; Ari Puspita (Infotek: Jurnal Informatika dan Teknologi, 2023)
The purchasing process at PT Primajaya Putra Mandiri has not been carried out effectively and efficiently. This becomes an obstacle in making purchase reports every month. For this reason, a purchasing information system design is required. Purchasing information systems can streamline the purchase transaction process and can produce more accurate and timely purchase reports and are able to record accounting transactions in a short time. Timely and accurate purchase reports are necessary for the decision-making process for business entity owners. The objective of this research is to develop software using the waterfall development method, so that it can produce software that is capable of improving the purchasing system. The development of information systems in the manufacture of software uses the Waterfall model and in the manufacture of this software uses JavaScript as the script language used to create desktop pages and MySQL as the database for data storage. The results of the design of a purchasing information system using the waterfall method can reduce errors caused by human factors (human error), avoid duplicate data entry and presentation of sales reports presented in a fast and precise time so as to help the owner to carry out the decisionmaking process